COMMUNITY EMPOWERMENT THROUGH BUSINESS PROGRAM FOR INCREASING COMMUNITY INCOME EMPOWERMENT OF FAMILY WELFARE IN MATTAPPAWALIE KELURAHAN PUJANANTING DISTRICT, BARRU - Muhammad, Mukmin; Satriana (P3M Stia Al Gazali Barru and Meraja media, 2022)
Copyright (c) 2022 Meraja journal